Co-culturing neural and bone mesenchymal stem cells in photosensitive hydrogel enhances spinal cord injury repair - Bai, Jianzhong; Liu, Guoping; Gao, Yang; Zhang, Xishan; Niu, Guoqi; Zhang, Hongtao (Frontiers in Bioengineering and Biotechnology, 2024)
In mammalian species, neural tissues cannot regenerate following severe spinal cord injury (SCI), for which stem cell transplantation is a promising treatment.Neural stem cells (NSCs) have the potential to repair SCI; however, in unfavourable microenvironments, transplanted NSCs mainly differentiate into astrocytes rather than neurons. In contrast, bone mesenchymal stem cells (BMSCs) promote the differentiation of NSCs into neurons and regulate inflammatory responses. Owing to their easily controllable mechanical properties and similarities to neural tissue, gelatin methacrylate (GelMA) hydrogels offer remarkable cell biocompatibility and regulate the differentiation of NSCs. Therefore, in this study, we propose co-culturing NSCs and BMSCs within low-modulus GelMA hydrogel scaffolds to promote regeneration following SCI. In vitro comparisons revealed that the viability, proliferation, migration, and neuron differentiation capacity of cells in these low-modulus scaffolds exhibit substantially superior performance compared to those in high-modulus hydrogel scaffolds. To the best of our knowledge, this study is the first to report that NSCs/BMSCs co-culture implants can remarkably enhance motor function recovery in SCI rats, reduce the area of spinal cord cavities, stimulate neuron regeneration, and suppress scar tissue formation. Thus, this hydrogel system loaded with co-cultured cells represents a promising therapeutic approach for SCI repair.